Is sodium a good hyperhydration strategy in 10k runners? - de Souza, R. F.; de Oliveira, L. S.; de Matos, D. G.; Moreira, O. C.; da Silva, T. C.; Chilibeck, P.; Reis Ferreira, A.; de Freitas Zanona, A.; Aidar, F. J. (Journal of Human Sport & Exercise, 2018)
The objective of the present study was to evaluate the effect of pre-exercise hyperhydration with sodium (PEHS), on the state of hydration and performance in runners of a 10K. Ten male runners (age 40.5 ± 9.7 yrs, weight 72.5 ± 8.4 kg, body fat 18.8 ± 4.5%) participated in the study and performed 10 km of street running under two different forms of prehydration: pre-exercise hydration (PEH), consisting of water intake ad libitum, and pre-exercise sodium hyperhydration (PEHS), consisting of sodium ingestion (12 mg of sodium for each 5 mL of water) diluted 1 h before the test. The variables evaluated were heart rate (HR), body temperature (BT), body mass (BM), blood pressure (BP), relative dehydration (RD), absolute dehydration (AD), total ingested water (TH2OING), degree of dehydration (DD), sweating rate (SR), specific gravity of urine (SGU), urine pH, and performance time (PT). There was no difference between intervention groups in the variables HR, BT, BM, BP, SGU, urine pH, and PT. RD (0.76 ± 0.41 kg vs. 1.16 ± 0.43 kg; Cohen`s d = 0.95; p = 0.042); AD (0.63 ± 0.36 kg vs. 0.99 ± 0.43 kg; Cohen`s d = 0.90; p = 0.038); DD (0.63 ± 0.52% vs. 1.35 ± 0.56%; Cohen`s d = 1.33; p = 0.009); SR (2255.03 ± 1297.25 mL vs. 3550.06 ± 1527.35 mL; Cohen`s d = 0.91; p = 0.048) were lower in the state of PEHS. PEH presented greater TH2OING (0.16 ± 0.12 mL vs. 0.34 ± 0.41 mL; Cohen`s d = 0.59; p = 0.008). It was concluded that PEHS produces better hydration in runners during long distance running.